2017
DOI: 10.1159/000475493
|View full text |Cite
|
Sign up to set email alerts
|

Renal-Limited “Lupus-Like” Nephritis: How Much of a Lupus

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by development of autoantibodies to nuclear and cytoplasmic antigens. A small subset of SLE patients who had the typical clinical features of SLE was reported to show persistently negative antinuclear antibody tests. Our report describes a 5-year-old male who presented with histopathological findings suggestive of lupus nephritis with no clinical signs or symptoms of SLE and negative autoantibodies. He was treated with corticosteroids, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Lupus nephritis encompasses a spectrum of glomerular, tubulointerstitial, and vascular changes occurring in patients with SLE. Despite its protean manifestations, some pathologic features of lupus nephritis are felt to be characteristic enough to allow authors to apply the term "lupus-like" to describe diverse entities including cases of apparently kidney-limited SLE, HIV-associated immune complex disease of the kidney, and even some cases of glomerulonephritis associated with HCV infection (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, the pathologic features used to label these cases as lupus-like are highly variable, reflecting a lack of formal criteria to diagnose lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lupus nephritis encompasses a spectrum of glomerular, tubulointerstitial, and vascular changes occurring in patients with SLE. Despite its protean manifestations, some pathologic features of lupus nephritis are felt to be characteristic enough to allow authors to apply the term "lupus-like" to describe diverse entities including cases of apparently kidney-limited SLE, HIV-associated immune complex disease of the kidney, and even some cases of glomerulonephritis associated with HCV infection (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). However, the pathologic features used to label these cases as lupus-like are highly variable, reflecting a lack of formal criteria to diagnose lupus nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, nearly 5% of the nonlupus nephritis glomerulopathies fulfilled three of the five criteria for lupus nephritis. Some of these patients may have a forme fruste of SLE, may meet criteria for SLE in the future, and have been variably referred to as "lupus-like nephritis" or "full-house nephropathy" in the literature (11)(12)(13)(14)(15)(16)(17)(18)(19). Such cases are highly heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…Maziad, et al, 19 reported in 2017 the case of a 5year-old Hispanic boy with nephritis lupus-like. The clinical presentation was edema, proteinuria and rapidly progressive glomerulonephritis requiring hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical course of our patients coincides with that reported in the literature with variable evolution and prognosis. [5][6][7]9,18,19 One case did not achieve remission due to discontinuation of treatment, persisted with proteinuria and deterioration of renal function with current creatinine in 2.4 mg/dL two years after kidney biopsy. Only one case, a 24-year-old woman, eight years after kidney biopsy and on maintenance therapy with an adequate response, had seroconversion during her first pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Extrarenal signs and symptoms of systemic lupus erythematosus (SLE), as well as serologic lupus antibody testing, are typically absent. [ 8 ].…”
Section: Introductionmentioning
confidence: 99%